2019
DOI: 10.1016/j.molmet.2019.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Targeted deletion of Tcf7l2 in adipocytes promotes adipocyte hypertrophy and impaired glucose metabolism

Abstract: Objective Activation of the Wnt-signaling pathway is known to inhibit differentiation in adipocytes. However, there is a gap in our understanding of the transcriptional network regulated by components of the Wnt-signaling pathway during adipogenesis and in adipocytes during postnatal life. The key intracellular effectors of the Wnt-signaling pathway occur through TCF transcription factors such as TCF7L2 (transcription factor-7-like 2). Several genetic variants in proximity to TCF7L2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
80
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(89 citation statements)
references
References 164 publications
(135 reference statements)
6
80
0
Order By: Relevance
“…Conversely, transgenic mice over-expressing Tcf7l2 displayed HFD-induced glucose intolerance (14). Contrasting these findings, targeted deletion of Tcf7l2 in mature adipocytes (mADs) resulted in enhanced adiposity, glucose intolerance and hyperinsulinaemia (11,12). In humans, TCF7L2 expression was decreased in the SC abdominal (hereafter referred to as abdominal) AT of subjects with impaired glucose tolerance (11) and reduced systemic insulin sensitivity (15).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Conversely, transgenic mice over-expressing Tcf7l2 displayed HFD-induced glucose intolerance (14). Contrasting these findings, targeted deletion of Tcf7l2 in mature adipocytes (mADs) resulted in enhanced adiposity, glucose intolerance and hyperinsulinaemia (11,12). In humans, TCF7L2 expression was decreased in the SC abdominal (hereafter referred to as abdominal) AT of subjects with impaired glucose tolerance (11) and reduced systemic insulin sensitivity (15).…”
Section: Introductionmentioning
confidence: 96%
“…More recently, the in vitro role of TCF7L2 in the regulation of adipogenesis was revisited with conflicting results. Whilst Chen et al showed that TCF7L2 knockdown (KD) in 3T3-L1 preadipocytes leads to impaired adipocyte differentiation (11) in another study inducible TCF7L2 deletion in immortalised inguinal mouse APs was associated with enhanced adipogenesis (12). Ex vivo adipose expression of Tcf7l2 was suppressed by high-fat diet (HFD)-induced and genetic obesity (12,13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although rs7903146 in TCF7L2 is not associated with changes in overall TCF7L2 transcription (i.e. of all isoforms), with conflicting data regarding the association of rs7903146 with specific TCF7L2 variant expression in subcutaneous fat [20][21][22], TCF7L2 expression has been shown to be reduced in adipose tissue from type 2 diabetes subjects [23] and in obese mice [24]. Additionally, surgery-induced weight loss has been shown to regulate alternative splicing of Tcf7l2 in adipose tissue [25].…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to understand the causal relationship between TCF7L2 and diabetes led to studies on several metabolic tissues, with the data suggesting that the combined effects of loss of TCF7L2 in multiple tissues may account for the diabetes phenotype [28]. For example, previous reports have described the impact of loss of TCF7L2 expression on adipocyte development and insulin sensitivity [24,29]. In the present study, we used a genetic model of ablation of TCF7L2 gene expression in mature adipocytes to determine whether TCF7L2 plays a role in adipocyte function, independent of its role in adipogenesis.…”
Section: Introductionmentioning
confidence: 99%